Language politeness performed by politicians in the discourse of jakarta election 2017 at online portal news - Widya Pangestika; Agustina Agustina; Ngusman Abdul Manaf (Fakultas Ilmu Pendidikan UNP)
Jakarta Election 2017 was a phenomenal one from many points of views including aspect of language use as political tool. Therefore, this study aims to describe the politeness level of politicians in the discourse of Jakarta election 2017 at online portal news. This research used a qualitative approach with descriptive method. Analyzing the data was exercised by content analysis method with the application of language politeness theory from Brown-Levinson and Leech. Based on data analysis, politicians are more dominant to convey their ideas through a rhetorical style of irony, expressive speech acts, and vague strategies; they also tend to violate rather than adhere to the politeness principle so, it was ‘high potential’ to threaten the face of the intended person or party. Based on the findings of this research, the level of language politeness performed by politicians in Jakarta Election is represented in three divisions; about 48% of comments of the politicians are at an ‘impolite’, 15% are at ‘less polite’ level, and only 36% are in the ‘polite’ category.